First genetic maps development and QTL mining in Ranunculus asiaticus L. through ddRADseq - Martina, Matteo; Acquadro, Alberto; Gulino, Davide; Brusco, Fabio; Rabaglio, Mario; Portis, Ezio; Lanteri, Sergio (Frontiers in Plant Science, 2022)
Persian Buttercup (Ranunculus asiaticus L.; 2x=2n=16; Genome size: 7.6Gb) is an ornamental and perennial crop native of Asia Minor and Mediterranean basin, marketed both as cut flower or potted plant. Currently new varieties are developed by selecting plants carrying desirable traits in segregating progenies obtained by controlled mating, propagated through rhizomes or micro-propagated. In order to escalate selection efficiency and respond to market requests, more knowledge of buttercup genetics would facilitate the identification of markers associated with loci and genes controlling key ornamental traits, opening the way for molecular assisted breeding. Reduced-representation sequencing (RRS) represents a powerful tool for plant genotyping, especially in case of large genomes, and have been applied for the development of high-density genetic maps in several species. We report on the development of the first molecular-genetic maps in R. asiaticus based on of a two-way pseudo-testcross strategy. A double digest restriction-site associated DNA (ddRAD) approach was applied for genotyping two F1 mapping populations, whose female parents were a genotype of a so called ‘ponpon’ and of a ‘double flower’ varieties, while the common male parental (‘Cipro’) was a genotype producing a simple flower. The ddRAD generated a total of ~2Gb demultiplexed reads, resulting in an average of 8,3M reads per line. The sstacks pipeline was applied for the construction of a mock reference genome based on sequencing data, and SNP markers segregating in only one of the parents were retained for map construction by treating the F1 population as a backcross. The four parental maps (two of the female parents and two of the common male parent) were aligned with 106 common markers and 8 linkage groups were identified, corresponding to the haploid chromosome number of the species. An average of 586 markers were associated with each parental map, with a marker density ranging from 1 marker/cM to 4.4 markers/cM. The developed maps were validated by performing a QTL analysis for flower color, leading to the identification of major QTLs for purple pigmentation. These results contribute to dissect on the genetics of Persian buttercup, enabling the development of new approaches for future varietal development.